2013
DOI: 10.1002/jgrd.50340
|View full text |Cite
|
Sign up to set email alerts
|

From pointwise testing to a regional vision: An integrated statistical approach to detect nonstationarity in extreme daily rainfall. Application to the Sahelian region

Abstract: [1] Global warming is expected to intensify the hydrologic cycle. Documenting whether significant changes in the extreme precipitation regimes have already happened is consequently one of the challenging topics in climatic research. The high natural variability of extreme precipitation often prevents from obtaining significant results when testing changes in the empirical distribution of extreme rainfall at regional scale. A regional integrated approach is proposed here as one possible answer to this complex m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 82 publications
4
10
0
1
Order By: Relevance
“…In the central Sahel, the stationary levels have barely been recovered so far. These results on extreme rainfall evolution in the central Sahel are coherent with Panthou et al () who found a significant decrease of around 10% in the 2 year return level of the periods 1950–1969 and 1970–1990. Over the recent decade, the evolution of the K ‐year return level in the central Sahel is also in line with the upward trend in daily rainfall maxima shown by Panthou et al ().…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In the central Sahel, the stationary levels have barely been recovered so far. These results on extreme rainfall evolution in the central Sahel are coherent with Panthou et al () who found a significant decrease of around 10% in the 2 year return level of the periods 1950–1969 and 1970–1990. Over the recent decade, the evolution of the K ‐year return level in the central Sahel is also in line with the upward trend in daily rainfall maxima shown by Panthou et al ().…”
Section: Resultssupporting
confidence: 90%
“…A change in the 1980s is found with a period of decreasing rainfall intensity between the 1950s and the 1970s, followed by a period of increasing intensity since the 1980s. This confirms previous results found for the central Sahel by Panthou et al () and Panthou et al (). It is also in line with the increasing trend in extreme rainfall detected since 1982 by Taylor et al () over the entire Sahel.…”
Section: Conclusion and Discussionsupporting
confidence: 93%
“…A regional trend detection technique (Panthou et al, 2013) can be employed to improve the signal to noise ratio in a future study. Also, other physical covariates can be considered to study the changes in extreme rainfall characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…3. Table 1 obtained for a much larger area in this region by Panthou et al (2012Panthou et al ( , 2013, working on the data of 126 daily rain gauges covering the period . Note also that the temporal scale exponent (η) is large (0.9), which means that the intensity strongly decreases as the duration increases.…”
Section: Regional Modelmentioning
confidence: 99%